2008
DOI: 10.3852/07-168
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and life cycle of a new species ofDidymium(Myxomycetes) from arid areas of Mexico

Abstract: A new species of myxomycete, Didymium umbilicatum, isolated from the bark of Agavaceae, is described from arid zones of Mexico. This species was obtained from moist chamber cultures of Yucca spp. bark, collected in four different years from two states (Puebla and Querétaro) in central Mexico and found in the field from Hidalgo, Oaxaca and Puebla on the dead remains of Agave sp. The new species has small, flat, white sporocarps or short plasmodiocarps, 0.2-1.3 mm diam, and 0.15-0.4 mm tall. They are sessile on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…; Wrigley de Basanta et al. , , , ). Phylogenetic relationships confirmed that Columellidia is composed of the paraphyletic Stemonitales and the monophyletic Physarales, with Echinosteliales as a sister group of both (Fiore‐Donno et al.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Wrigley de Basanta et al. , , , ). Phylogenetic relationships confirmed that Columellidia is composed of the paraphyletic Stemonitales and the monophyletic Physarales, with Echinosteliales as a sister group of both (Fiore‐Donno et al.…”
Section: Discussionmentioning
confidence: 97%
“…), 51 d for Didymium umbilicatum D. Wrigley, Lado & Estrada (Wrigley de Basanta et al. ), 40 d for Didymium operculatum D. Wrigley, Lado & Estrada (Wrigley de Basanta et al. ), 6 d for Didymium annulisporum H.W.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research carried out in the Patagonian steppe registered 133 different species (Lado & al., 2014), almost the 15% of the total number of species known worldwide. These arid regions have become even more interesting because of the number of new species that have been discovered and described from them (Lado & al., 1999(Lado & al., , 2007(Lado & al., , 2013(Lado & al., , 2014Estrada-Torres & al., 2001, 2009Wrigley de Basanta & al., 2008b, 2009, 2010a, 2015. These new species represent four different orders, and the genera Cribraria, Didymium, Licea, Macbrideola, Perichaena and Physarum. Since the publication of the first records by Rudolphi (1829), only 31 species of myxomycete had been published from Peru, until a recent paper increased the number to 80 (Rojas & al., 2011), but almost all of these records were from the tropical forests of the Amazon basin, to the East of the Peruvian Andes.…”
Section: Introductionmentioning
confidence: 99%